Cross-Reactive Antibodies With the Capacity to Mediate HIV-1 Envelope Glycoprotein–Targeted Antibody-Dependent Cellular Cytotoxicity Identified in HIV-2–Infected Individuals. (2nd February 2019) - Karlsson, Ingrid; Tingstedt, Jeanette Linnea; Şahin, Gülşen Özkaya; Hansen, Mikkel; Szojka, Zsofia; Buggert, Marcus; Biague, Antonio; Da Silva, Zacharias; Månsson, Fredrik; Esbjörnsson, Joakim; Norrgren, Hans; Medstrand, Patrik; et al.
Abstract: Disease progression of human immunodeficiency virus type 1 (HIV-1) is delayed by HIV type 2 (HIV-2) in individuals with dual HIV-1/HIV-2 infection. The protective mechanisms, however, are still to be revealed. In the current study we examined type-specific and cross-reactive antibody-dependent cellular cytotoxicity (ADCC) in HIV-1 and HIV-2 monoinfection or dual infection. Of note, intertype cross-reactive antibodies that mediated HIV-1 envelope glycoprotein (Env)–targeted ADCC were frequently identified in HIV-2–infected individuals. Furthermore, the magnitude of HIV-1 cross-reactive ADCC activity during HIV-2 infections depended on the HIV-1 Env origin and was associated with the duration of infection. These results suggest that preexisting antibodies against HIV-2, which mediate intertype ADCC, might contribute to control of HIV-1 during dual infection. Abstract : Antibody-dependent cellular cytotoxicity (ADCC) was analyzed in human immunodeficiency virus (HIV) 1 and 2 infections. Cross-reactive antibodies that mediated HIV-1 envelope glycoprotein–targeted ADCC were identified in HIV-2–infected individuals, suggesting that preexisting HIV-2 antibodies might help control HIV-1 during dual infection.